Pisava = latinica - Pogačnik, Aleš (Jezik in slovstvo, 2006)
The starting point of the article is that writing is the first political fact of language. It describes the current situation in written communication around the world, in particular those languages with a short or non-existent written tradition. Through examples it highlights some pattern dilemmas on written norms. These dilemmas concern differentiation between dialect/socio-dialect, Pidgin, Creole and language, establishment of a writtennorm, and the choice of writing, especially for the main languages of young states that have only recently ascribed a special status to these languages. In the conclusion, the article points out the inefficiency of written reforms for languages, which use the leading alphabet of the modern world, the Latin alphabet, and also discusses the questionable nature of the Slovene written reform on borrowing foreign words, which wrongly presumes that in the Latin alphabet a single sound.
Keywords: latinica; pisave